KONSEP RUMAH LEBAH DALAM AL-QUR'AN - Priyanto, Afif Dani (Sekolah Tinggi Ilmu Al-Quran dan Sains Al-Ishlah, 2024)
This research discusses the concept of beehives in the Qur'an. Bees are insects mentioned in the Qur'an with many uniqueness, one of which is honey. The focus of this research is to examine the concept of beehives with the study of Al-Qur'an Surah al-Nahl [16]: 68-69. This research uses the library research method, which makes all written works as a reference for writing. The result of this research is the concept of beehive in the Qur'an with the focus of the study of Al-Qur'an Surah al-Nahl [16]: 68-69 it has a hesakgonal shape. Inseparable from the study, the secret behind the hexagonal shape is described in three aspects. Firstly, it is strong against a pressure. Second, it matches the legs of a bee that has six legs. Third, it is able to create a warm and cosy space.